GOVERNMENT IN ISLAM - Saepul Rizal; Agung Nurrahman (Jurnal Ilmiah Wahana Bhakti Praja, 2021)
Governance in Islam is an interesting topic to discuss considering that today many countries, with all their advantages and disadvantages, are looking for an ideal government model that can be easily implemented. Government in relying on the principles of the Qur'an and Sunnah without seeing whether these principles are in line with or different from other systems of government, and without paying attention to history which has had an impact and gave rise to different conditions and in the current era which is relatively mixed with these principles. This article discusses Islam and government, then the state is part of the teachings of Islam, and that one of its goals is to establish government, uphold justice, and liberate people from all forms of colonialism in all aspects of their lives. Then discuss the basics of the establishment of the state, which refers to the basics of belief and the basics of government organization. Then discuss the function of an Islamic state and the basic rights in it, and finally talk about the characteristics of an Islamic state.